Factors influencing burnout, stress levels, and coping strategies among nursing staff in intensive care units - Wudarczyk, Beata; Krupa-Nurcek, Sabina; Czapla, Michał; Uchmanowicz, Izabella (Frontiers in Public Health, 2025)
IntroductionProfessional burnout among nurses, particularly in intensive care units, is a significant issue affecting both healthcare professionals and patient care quality. It contributes to increased medical errors and diminished care standards. The objective of this study was to evaluate factors influencing professional burnout in nursing staff working in intensive care units.MethodologyThis quantitative study was conducted between March and November 2019 among nurses undergoing qualification and specialization training at the European Centre for Postgraduate Education in Wrocław. A total of 286 questionnaires were collected, with 282 valid responses after excluding incomplete questionnaires (1.4%). Standardized tools used included the Maslach Burnout Inventory (MBI), Perceived Stress Scale (PSS-10), and the Mini-COPE Stress Coping Inventory. Participation was anonymous and voluntary, with informed consent obtained from all respondents.ResultsThe study included 282 respondents, with women comprising 93.62% of the participants. The average burnout score based on the MBI was 39.78 out of 100 (SD = 20.7). According to the PSS-10, 43.26% of respondents experienced high stress, 36.88% medium stress, and 19.86% low stress. The Mini-COPE results indicated frequent use of Active Coping and Planning strategies, while strategies like Denial and Substance Use were used infrequently. Regarding life satisfaction (SWLS), 41.84% of participants had medium, 32.27% high, and 25.89% low life satisfaction.ConclusionProfessional burnout among nursing staff is a multifaceted issue closely related to stress levels, coping mechanisms, and overall life satisfaction. Addressing burnout requires comprehensive approaches that consider these interrelated factors.Practical implicationsTo reduce burnout among ICU nurses, healthcare institutions should integrate routine stress assessments and provide structured support systems, such as resilience training and peer support programs. These interventions can enhance nurses’ ability to manage stress, decrease emotional exhaustion, and ultimately improve the quality of care delivered to patients in high-stress environments like intensive care units.